3, September 2012 1
ISSN 2277  5048  2012 Bonfring
Abstract There is many subclasses of analytic and
univalent functions. A class T of functions with negative
coefficients introduced by Silverman [8] opened up a new and
fruitful line of research in the theory of univalent functions.
Following the works of Khairnar and Meena More [3],
Aghalary and Kulkarni [1], Silverman and Silvia [8] and Owa
and Nishiwaki [5] on analytic and univalent functions, in this
paper we introduce two new classes for a family of analytic
function with negative coefficients. We have attempted to
obtain coefficient estimate, distortion theorem and extreme
points for the class TSn(o, , , ) and TKn(o, , , ) for z <
1, 0 <  s 1,
2
1
s s 1, 0 s o s
2
1
and
2
1
< s 1.
Keywords Convex Functions, Salagean Operator,
Starlike Functions, Univalent Functions
I. INTRODUCTION
HE classical field of analytic univalent function of a
complex variable which is classified under geometric
function theory. Due to interesting connections with geometry
and analysis continues to attract active research by function
theorists.
In the investigation of an analytic function there resulted a
new direction of research in this theory namely, construction
of subclasses of analytic univalent function is trying to settle a
well known conjecture known as the Bieberbach conjecture
which was positively settled by Branges [2] in 1985.
Let A denote the class of functions given by
=
+ =
2 j
j
j
z a z f(z) (1.1)
Which are analytic in the unit disc E: {z: z < 1} and
normalized by f (0) = 0, 1 (0) f = ' and let S be the subclass of
A consisting of analytic and univalent functions of the form
(1.1).
We denote by S
*
(o), K (o), consisting of all functions
which are, respectively star like and convex of order o in E
with 0 s o < 1. Thus
T.V. Sudharsan, Department of Mathematics, SIVET College,
Chennai  600 073, India. Email: tvsudharsan@rediffmail.com
R. Vijaya, Department of Mathematics, S.D.N.B. Vaishnav College,
Chennai  600 044, India. Email: viji_dorai67@yahoo.co.in
DOI: 10.9756/BIJDM.1297
)
`
e < s >


.

\
 '
e = E z 1, 0 :
f(z)
(z) f z
Re : S f ) ( S
*
. E z 1, 0 :
(z) f
(z) f z
1 Re : S f ) K(
)
`
e < s >


.

\

'
' '
+ e =
The subfamily T of S consists of functions of the form
0) (a z a z f(z)
j
2 j
j
j
> =
=
(1.2)
For functions f(z) e S, Salagean [6] introduced a new
differential operator called Salagean differential operator D
n
defined by D
n
: A A, n e N
N e =
' = =
=
The basic classes of convex functions, starlike functions,
functions with negative coefficients and many other
introduced and several properties like the coefficient problem,
radius of convexity problem and so on have been investigated.
In this paper using Salagean operator D, we introduce the
classes TS
n
(o, , , ) and TK
n
(o, , , ) and obtain sharp
results for coefficient estimates. This leads to extremal
properties. We also obtain growth and distortion theorem.
Definition 1.1 A function f e T is said to be in the class
TS
n
(o, , , ) if and only if
1
f(z) D
f(z) D
f(z) D
f(z) D
2
1
f(z) D
f(z) D
n
1 n
n
1 n
n
1 n
<


.

\



.

\

+ +
+
For z < 1, 0 <  s 1,
2
1
s s 1, 0 s o s
2
1
and
2
1
< s
1.
If n = 0, we obtain the corresponding result of Khairnar
and Meena More [3].
If we replace by 1, n = 0, in the above inequality, we
obtain the results of Aghalary and Kulkarni [1] and Silverman
and Silvia [8].
If we replace by 1, n = 0, we obtain the results of Owa
and Nishiwaki [5].
On Certain Subclasses of Analytic and Univalent
Functions based on an Extension of Salagean
Operator
T.V. Sudharsan and R. Vijaya
T
Bonfring International Journal of Data Mining, Vol. 2, No. 3, September 2012 2
ISSN 2277  5048  2012 Bonfring
Furthermore, a function f(z) is said to belong to the class
TK
n
(o, , , ) if and only if (z) f z ' e TS
n
(o, , , ).
II. COEFFICIENT ESTIMATES AND OTHER PROPERTIES
Theorem 2.1 Let f be defined by
0) (a z a z f(z)
j
2 j
j
j
> =
=
is in TS
n
(o, , , ) if and only if
) (1 2 )]a j j j 2 j (2 ) j [(j
2 j
j
n 1 n 1 n n n 1 n
s +
=
+ + +
(2.1)
Proof Suppose
) (1 2 )]a j j j 2 j (2 ) j [(j
2 j
j
n 1 n 1 n n n 1 n
s +
=
+ + +
We have
0 f(z)) D f(z) (D f(z)) D f(z) (D 2
f(z) D f(z) D
n 1 n n 1 n
n 1 n
<
+ +
+
With the provision
0 z )a j j j 2 j (22 ) (1 2
z )a j [(j
2 j
j
j
n 1 n 1 n n
2 j
j
j
n 1 n
< +
=
+ +
=
+
(2.2)
For z = r < 1, then the condition (2.2) is bounded above
by
0
) (1 2 )]a j j j 2 j (2 ) j [(j
) (1 2
r )]a j j j 2 j (2 ) j [(j
r )a j j j 2 j (22
) (1 2 r )a j (j
2 j
j
n 1 n 1 n n n 1 n
2 j
j
j
n 1 n 1 n n n 1 n
2 j
j
j
n 1 n 1 n n
2 j
j
j
n 1 n
s
+ s
+ =
+
=
+ + +
=
+ + +
=
+ +
=
+
) (1 2 )]a j j j 2 j (2 ) j [(j
2 j
j
n 1 n 1 n n n 1 n
s +
=
+ + +
f(z) e TS
n
(o, , , ).
Conversely, let f(z) e TS
n
(o, , , ).
Then from the definition of f(z), we have
1
f(z) D
f(z) D
f(z) D
f(z) D
2
1
f(z) D
f(z) D
n
1 n
n
1 n
n
1 n
<


.

\



.

\

+ +
+
that is,
z )a j j ( ] z )a j j ( ) [z(1 2
z )a j j (
2 j
j
j
n 1 n
2 j
j
j
n 1 n
2 j
j
j
n 1 n
<
+
=
+
=
+
=
+
As Re f(z) s z for all z, we have
z )]a j j j 2 j [2 ) z(1 2
z )a j j (
Re
2 j
j
j
n 1 n 1 n n
2 j
j
j
n 1 n
<
+ +
=
+ +
=
+
we choose the values of z on real axis, such that
f(z) D
f(z) D
n
1 n+
is real and upon clearing, the denominator of the above
expression and allowing z 1 through real values, we obtain
0 ) (1 2
)]a j j j 2 j (2 ) j [(j
2 j
j
n 1 n 1 n n n 1 n
s
+
=
+ + +
). (1 2
)]a j j j 2 j (2 ) j [(j
2 j
j
n 1 n 1 n n n 1 n
s
+
=
+ + +
Remark 2.1. If f(z) e TS
n
(o, , , ), then
2,3,... j for
) j j j 2 j (2 ) j (j
) (1 2
a
)] j j j 2 j (2 ) j [(j
) (1 2
a
n 1 n 1 n n n 1 n
j
2 j
n 1 n 1 n n n 1 n
j
=
+
s
+
s
+ + +
=
+ + +
and equality holds for
j
n 1 n 1 n n n 1 n
z
) j j j 2 j (2 ) j (j
) (1 2
z f(z)
+
=
+ + +
.
Corollary 2.1. If f(z) e TS
n
(o, , , 1)
2,3,... j for
) j j j 2 j (2 ) j (j
) (1 2
a
n 1 n 1 n n n 1 n
j
=
+
s
+ + +
and equality holds for
j
n 1 n 1 n n n 1 n
z
) j j j 2 j (2 ) j (j
) (1 2
z f(z)
+
=
+ + +
Corollary 2.2. If f(z) e TS
n
(o, , 1, 1),
2,3,... j for
) j j j (2 ) j (j
) (1 2
a
n 1 n n n 1 n
j
=
s
+ +
And equality holds for
Bonfring International Journal of Data Mining, Vol. 2, No. 3, September 2012 3
ISSN 2277  5048  2012 Bonfring
j
n 1 n n n 1 n
z
) j j j (2 ) j (j
) (1 2
z f(z)
=
+ +
Corollary 2.3 If f(z) e TS
n
(o, 1, 1, 1),
) j (j
) (1
a
n 1 n
j
o
s
+
Theorem 2.2 A function 0) (a , z a z f(z)
j
2 j
j
j
> =
=
is in
TK
n
(o, , , ) if and only if
) (1 2
)]a j j j 2 j (2 ) j [(j j
2 j
j
n 1 n 1 n n n 1 n 1 n
s
+
=
+ + + +
Proof The proof of this theorem is analogous of Theorem
2.1, because a function f(z) e TK
n
(o, , , ) if and only if
(z) f z ' e TS
n
(o, , , ), so it is enough that a
j
is replaced by
j
n+1
a
j
in Theorem 2.1.
Remark 2.2 If f(z) e TK
n
(o, , , ), then
2,3,... j for
)] j j j 2 j (2 ) j [(j j
) (1 2
a
n 1 n 1 n n n 1 n 1 n
j
=
+
s
+ + + +
and equality holds for
j
n 1 n 1 n n n 1 n 1 n
z
)] j j j 2 j (2 ) j [(j j
) (1 2
z f(z)
+
=
+ + + +
Corollary 2.4. If f(z) e TK
n
(o, , , 1)
2,3,... j for
)] j j j 2 j (2 ) j [(j j
) (1 2
a
n 1 n 1 n n n 1 n 1 n
j
=
+
s
+ + + +
and equality holds for
j
n 1 n 1 n n n 1 n 1 n
z
)] j j j 2 j (2 ) j [(j j
) (1 2
z f(z)
+
=
+ + + +
Corollary 2.5. If f(z) e TK
n
(o, , 1, 1)
2,3,... j for
)] j j j (2 ) j [(j j
) (1 2
a
n 1 n n n 1 n 1 n
j
=
s
+ + +
and equality holds for
j
n 1 n n n 1 n 1 n
z
)] j j j (2 ) j [(j j
) (1 2
z f(z)
=
+ + +
Corollary 2.6. If f(z) e TK
n
(o, 1, 1, 1)
)] j [(j j
) (1
a
n 1 n 1 n
j
s
+ +
III. GROWTH AND DISTORTION THEOREM
Theorem 3.1. If f(z) e TS
n
(o, , , ), then
. r
) 2 2 2 2 2 (2 ) 2 (2
) (1 2
r
f(z) r
) 2 2 2 2 2 (2 ) 2 (2
) (1 2
r
2
n 1 n 1 n n n 1 n
2
n 1 n 1 n n n 1 n
+
+ s
s
+
+ + +
+ + +
(3.1)
Equality holds for
)] 2 ( ) 4 [(1
) (1 2
z f(z)
+ +
= (3.2)
Proof. By Theorem 2.1, we have f(z) e TS
n
(o, , , ) if
and only if
) (1 2 )]a j j j 2 j (2 ) j [(j
2 j
j
n 1 n 1 n n n 1 n
s +
=
+ + +
or equivalently,
2 1
) (1 2
]a
2 1
)j (1 2
j [j
2 j
j
n
n 1 n
+
s


.

\

+
=
+
Let .
2 1
) (1 2
j t
n
+
=
f(z) e TS
n
(o, , , ) if and only if
t j t)a (j
n
2 j
j
1 n
s
=
+
(3.3)
where
2 1
) (1 2
j t
n
+
=
when j = 2,
t. 2
t)a (j t)a (2
n
2 j
j
1 n
2 j
j
1 n
s
s
=
+
=
+
This last inequality follows from (3.3). We obtain
.
t 2
t 2
r r
a r r r a r f(z)
1 n
n
2
2 j
j
2
2 j
j
j


.

\

+ s
+ s + s
+
=
Similarly
.
t 2
t 2
r r
a r r r a r f(z)
1 n
n
2
2 j
j
2
2 j
j
j


.

\

>
> >
+
=
So,
2
1 n
n
2
1 n
n
r
t 2
t 2
r f(z) r
t 2
t 2
r


.

\

+ s s


.

\

+ +
That is
Bonfring International Journal of Data Mining, Vol. 2, No. 3, September 2012 4
ISSN 2277  5048  2012 Bonfring
. r
) 2 2 2 2 2 (2 ) 2 (2
) (1 2
r
f(z) r
) 2 2 2 2 2 (2 ) 2 (2
) (1 2
r
2
n 1 n 1 n n n 1 n
2
n 1 n 1 n n n 1 n
+
+ s
s
+
+ + +
+ + +
Hence the theorem.
Corollary 3.1. When n = 0, we obtain the results of
Khainar and Meena More [3]
2
2
r
) 2 ( ) 4 (1
) (1 2
r
f(z) r
) 2 ( ) 4 (1
) (1 2
r
+ +
+ s
s
+ +
Corollary 3.2. If f(z) e TS
0
(o, , , 1), then
2
2
r
) 2 (1 ) 4 (1
) (1 2
r
f(z) r
) 2 (1 ) 4 (1
) (1 2
r
+ +
+ s
s
+ +
with equality for
r z at z
) 2 (1 ) 4 (1
) (1 2
z f(z)
2
=
+ +
=
Corollary 3.3. If f(z) e TS
0
(o, , 1, 1), then
2 2
r
2 3 1
) (1 2
r f(z) r
2 3 1
) (1 2
r
+
+ s s
+
and equality holds for
r z at z
2 3 1
) (1 2
z f(z)
2
=
+
=
Theorem 3.2. If f(z) e TK
n
(o, , , ), then
. r
)] 2 2 2 2 2 (2 ) 2 [(2 2
) (1 2
r
f(z) r
)] 2 2 2 2 2 (2 ) 2 [(2 2
) (1 2
r
2
n 1 n 1 n n n 1 n 1 n
2
n 1 n 1 n n n 1 n 1 n
+
+ s
s
+
+ + + +
+ + + +
Proof. The proof of this theorem is analogous to that of
Theorem 3.1 because a function f(z) e TK
n
(o, , , ) if and
only if (z) f z ' e TS
n
(o, , , ). So it is enough to replace a
j
by j
n+1
a
j
in Theorem 3.1.
Corollary 3.4. When n = 0, we obtain the results of
Khainar and Meena More [3]
2 2
r
) 2 ( ) 4 (1
) (1
r f(z) r
) 2 ( ) 4 (1
) (1
r
+ +
+ s s
+ +
Corollary 3.5. If f(z) e TK
0
(o, , , 1), then
2 2
r
) 2 (1 ) 4 (1
) (1
r f(z) r
) 2 (1 ) 4 (1
) (1
r
+ +
+ s s
+ +
with equality holds for
r. z at z
) 2 (1 ) 4 (1
) (1
z f(z)
2
=
+ +
=
This result is due to [1] and [4].
Corollary 3.6. If f(z) e TK
0
(o, , 1, 1), then
2 2
r
2 3 1
) (1
r f(z) r
2 3 1
) (1
r
+
+ s s
+
with equality holds for
r. z at z
2 3 1
) (1
z f(z)
2
=
+
=
This result is due to [5].
Theorem 3.3. If f(z) e TS
n
(o, , , ), then
r
) 2 2 2 2 2 (2 ) 2 (2
) (1 4
1
(z) f r
) 2 2 2 2 2 (2 ) 2 (2
) (1 4
1
n 1 n 1 n n n 1 n
n 1 n 1 n n n 1 n
+
+ s
' s
+
+ + +
+ + +
(3.4)
Proof. Since f(z) e TS
n
(o, , , ), we have
t. j t)a (j
n
2 j
j
1 n
s
=
+
(3.5)
Where .
2 1
)j (1 2
j t
n
n
+
=
In view of Theorem 3.1, we have


.

\

+ s
+ =
+
=
+
=
+
t j
t j
t t) (j
a t t)a (j a j
1 n
n
n
2 j
j
2 j
j
1 n
2 j
j
1 n
When j = 2,


.

\

+ s
+
=
+
t 2
t 2
t t) (2 a j
1 n
n
n
2 j
j
1 n
Therefore
(
(


.

\

+ + s
+ s '
+
t 2
t 2
t t) (2 r 1
z ja 1 (z) f
1 n
n
n
2 j
1 j
j
Similarly
(
(


.

\

+ > '
+
t 2
t 2
t t) (2 r 1 (z) f
1 n
n
n
So
(
(


.

\

+ + s ' s
(
(


.

\

+
+ +
t 2
t 2
t t) (2 r 1 (z) f
t 2
t 2
t t) (2 r 1
1 n
n
n
1 n
n
n
(3.6)
Substituting t we have
Bonfring International Journal of Data Mining, Vol. 2, No. 3, September 2012 5
ISSN 2277  5048  2012 Bonfring
r
) 2 2 2 2 2 (2 ) 2 (2
) (1 4
1
(z) f r
) 2 2 2 2 2 (2 ) 2 (2
) (1 4
1
n 1 n 1 n n n 1 n
n 1 n 1 n n n 1 n
+
+ s
' s
+
+ + +
+ + +
Corollary 3.7. When n = 0, we obtain the results of
Khainar and Meena More [3]

.

\

+ s ' s 
.

\

t 2
t) 2(1
r 1 (z) f
t 2
t) 2(1
r 1
Substituting t, from (3.5) in (3.6), we obtain
r
) (2 2 ) (1
) (1 4
1 (z) f r
) (2 2 ) (1
) (1 4
1
+
+ s ' s
+
Corollary 3.8. If f(z) e TS
0
(o, , , 1), then
r
) (2 2 ) (1
) (1 4
1 (z) f r
) (2 2 ) (1
) (1 4
1
+
+ s ' s
+
Corollary 3.9. If f(z) e TS
0
(o, , 1, 1), then
r
2 3 1
) (1 4
1 (z) f r
2 3 1
) (1 4
1
+
+ s ' s
+
Theorem 3.4. If f(z) e TK
n
(o, , , ), then
r
)] 2 2 2 2 2 (2 ) 2 [(2 2
) (1 4
1
(z) f r
)] 2 2 2 2 2 (2 ) 2 [(2 2
) (1 4
1
n 1 n 1 n n n 1 n 1 n
n 1 n 1 n n n 1 n 1 n
+
+ s
' s
+
+ + + +
+ + + +
Proof. The proof of this theorem is similar to that of
Theorem 3.3, because a function f(z) e TK
n
(o, , , ) if and
only if (z) f z ' e TS
n
(o, , , ). i.e., replacing a
j
by j
n+1
a
j
in
Theorem 3.3.
Corollary 3.10. When n = 0, we obtain the results of
Khainar and Meena More [3]
r
) (2 2 ) (1
) (1 2
1 (z) f r
) (2 2 ) (1
) (1 2
1
+
+ s ' s
+
Corollary 3.11. If f(z) e TK
0
(o, , , 1), then
r
) (2 2 ) (1
) (1 2
1 (z) f r
) (2 2 ) (1
) (1 2
1
+
+ s ' s
+
Corollary 3.12. If f(z) e TK
0
(o, , 1, 1), then
r
2 3 1
) (1 2
1 (z) f r
2 3 1
) (1 2
1
+
+ s ' s
+
IV. EXTREME POINTS FOR TSN (o, , , )
The determination of the extreme points of a family of
univalent functions enables us to solve many extremal
problems.
Theorem 4.1. Let f
1
(z) = z and
2,3,4,... j for
z
) j j j 2 j (2 ) j (j
) (1 2
(z) f
j
n 1 n 1 n n n 1 n
j
=
+
=
+ + +
Then f(z) e TK
n
(o, , , ) if and only if f(z) can be
expressed in the forms
=
=
1 j
j j
(z) f f(z)
Where
j
> 0 and 1.
1 j
j
=
=
Proof. Let , (z) f f(z)
1 j
j j
=
=
j
> 0, j = 1, 2, with
1.
1 j
j
=
=
+ + +
=
(
+
+ =
+ =
=
2 j
j
n 1 n 1 n n n 1 n
j 1
2 j
j j 1 1
1 j
j j
z
) j j j 2 j (2 ) j (j
) (1 2
z (z)
(z) f (z) f
(z) f f(z)
that is,
=
+ + +
+
=
2 j
j
n 1 n 1 n n n 1 n
j
z
) j j j 2 j (2 ) j (j
) (1 2
z f(z)
Then
1. 1
) (1 2
) j j j 2 j (2 ) j (j
)] j j j 2 j (2 ) j [(j
) (1 2
1
2 j
j
n 1 n 1 n n n 1 n
2 j
n 1 n 1 n n n 1 n
j
s =
=
+ + +
=
+ + +
f(z) e TK
n
(o, , , ).
Conversely, suppose f(z) e TK
n
(o, , , ), then remark of
Theorem 2.1 gives us
) j j j 2 j (2 ) j (j
) (1 2
a
n 1 n 1 n n n 1 n
j
+
s
+ + +
we take
2,3,4,... j , a
) (1 2
) j j j 2 j (2 ) j (j
j
n 1 n 1 n n n 1 n
j
=
+
=
+ + +
and
1
= 1 .
2 j
j
=
Bonfring International Journal of Data Mining, Vol. 2, No. 3, September 2012 6
ISSN 2277  5048  2012 Bonfring
Then . (z) f f(z)
1 j
j j
=
=
Corollary 4.1. When n = 0, we obtain the result of
Khairnar and Meena More [3]. That is, f
1
(z) = z,
2,3,... j for ,
) j j 2 (2 1) (j
) (1 2
(z) f
j
=
+
=
Corollary 4.2. If f
1
(z) = z and
2,3,... j for z
) 1 j j 2 (2 1) (j
) (1 2
z (z) f
j
j
=
+
=
Then f(z) e TK
n
(o, , , 1) if and only if, f(z) can be
expressed in the form,
, (z) f f(z)
1 j
j j
=
= where
j
> 0, j = 1, 2, , . 1
1 j
j
=
=
This result is due to [1] and [4].
Corollary 4.3. If f
1
(z) = z and
2,3,... j for z
1) j (2 1) (j
) (1 2
z (z) f
j
j
=
=
Then f(z) e TK
n
(o, , 1, 1) if and only if, f(z) can be
expressed in the form,
, (z) f f(z)
1 j
j j
=
= where
j
> 0, j = 1, 2, , . 1
1 j
j
=
=
This result is due to Kulkarni [4].
Corollary 4.4. If f
1
(z) = z and
.
j
z
z (z) f
j
j
=
Then f(z) e TK
n
(0, 1, 1, 1) if and only if, f(z) can be
expressed in the form,
, (z) f f(z)
1 j
j j
=
= where
j
> 0, j = 1, 2, , . 1
1 j
j
=
=
V. CONCLUSION
In this paper making use of the Salagean differential
operator, new subclasses of analytic and univalent functions
are introduced for the functions with negative coefficients.
Many subclasses which are already studied by various
researchers are obtained as special cases of our two new
subclasses. We have obtained various properties such as
coefficient estimates, growth and distortion theorem for the
class of functions. Further new subclasses may be possible
from the two classes introduced in this paper.
REFERENCES
[1] R. Aghalary and S. Kulkarni, Some theorems on univalent functions,
J. Indian Acad. Math., Vol. 24, No. 1, Pp. 8193, 2002.
[2] L. de Branges, A proof of Bieberbach conjecture, Acta Math., Vol. 154,
No. 12, Pp. 137152, 1985.
[3] S.M. Khairnar and Meena More, Certain family of analytic and
univalent functions with normalized conditions, Acta Mathematica
Academiae Paedagogicae, Vol. 24, Pp. 333344, 2008.
[4] S.R. Kulkarni, Some problems connected with univalent functions,
Ph.D. Thesis, Shivaji University, Kolhapur, 1981.
[5] S. Owa and J. Nishiwaki, Coefficient Estimates for certain classes of
analytic functions, J. Inequal. Pure Appl. Math., Vol. 3, No. 5, Article
72, 5pp (electonic), 2002.
[6] G.S. Salagean, Subclasses of univalent functions, Lecture Notes in
Mathematics, Volume 1013, SpringerVerlag, Berlin, Pp. 362372,
1983.
[7] H. Silverman, Univalent functions with negative coefficients, Proc.
Amer. Math. Soc., Vol. 51, Pp. 109116, 1975.
[8] H. Silverman and E. Silvia, Subclasses of prestarlike functions, Math.
Japon, Vol. 29, No. 6, Pp. 929935, 1984.